Hepatitis B and HIV: prevalence, AIDS progression, response to highly active antiretroviral therapy and increased mortality in the EuroSIDA cohort - Konopnicki, Deborah; Mocroft, Amanda; de Wit, S; Antunes, Francisco; Ledergerber, Bruno; Katlama, Christine; Zilmer, K; Vella, Stefano; Kirk, Ole; Lundgren, Jens D (AIDS (London), 2005)
Whether hepatitis B (HBV) coinfection affects outcome in HIV-1-infected patients remains unclear. To assess the prevalence of HBV (assessed as HBsAg) coinfection and its possible impact on progression to AIDS, all-cause deaths, liver-related deaths and response to highly active antiretroviral therapy (HAART) in the EuroSIDA cohort. Data on 9802 patients in 72 European HIV centres were analysed. Incidence rates of AIDS, global mortality and liver-related mortality, time to 25% CD4 cell count increase and time to viral load < 400 copies/ml after starting HAART were calculated and compared between HBsAg-positive and HBsAg-negative patients. HBsAg was found in 498 (8.7%) patients. The incidence of new AIDS diagnosis was similar in HBsAg-positive and HBsAg-negative patients (3.3 and 3.4/100 person-years, respectively) even after adjustment for potential confounders: the incidence rate ratio (IRR) was 0.94 [95% confidence interval (CI), 0.74-1.19; P = 0.61]. The incidences of all-cause and liver-related mortalities were significantly higher in HBsAg-positive subjects (3.7 and 0.7/100 person-years, respectively) compared with HBsAg-negative subjects (2.6 and 0.2/100 person-years, respectively). The adjusted IRR values were 1.53 for global (95% CI, 1.23-1.90; P = 0.0001) and 3.58 for liver-related (95% CI, 2.09-6.16; P < 0.0001) mortality. HBsAg status did not influence viral or immunological responses among the 1679 patients starting HAART. The prevalence of HBV coinfection was 9% in the EuroSIDA cohort. Chronic HBV infection significantly increased liver-related mortality in HIV-1-infected patients but did not impact on progression to AIDS or on viral and immunological responses to HAART.